SUATU KRITERIA STABILISASI SISTEM DESKRIPTOR LINIER KONTINU REGULAR - Sari, Yulian (PYTHAGORAS : Jurnal Program Studi Pendidikan Matematika, 2014)
Abstract.The regular descriptor linear time-invariant system, or shorthandly this system is denoted by  are used in many applications, especially in mathematical modeling for engineering, biology, and economics. In this paper, the characterization of stabilization of this systems. Feedback control  for some  and  is used for stabilizing the system  such that the closed-loop system  is stable. Some examples is given to illustrate this characteristic. Keywords: regular descriptor linear time-invariant system, stabilization, stabilizable.